Vai trò của oxi trong phản ứng khử chọn lọc NOx bằng C3H6 trên xúc tác Cu/ZSM-5 - Sơn, Lê Thanh (Vietnam Journal of Chemistry, 2014)
The role of oxygen in selective reduction of NOx by C3H6 in the presence of oxygen over Cu/ZSM-5 catalyst was investigated by the temperature programmed surface reaction (TPSR). It was found that oxygen enhances the oxidation of NO by C3H6 to NO2, but also consumes C3H6 as an oxidative agent causing a decrease in the decomposition of NOx. The present results allow demonstrating the reaction mechanism of selective reduction of NOx by C3H6 in real conditions.